2016
DOI: 10.1186/s13058-016-0687-3
|View full text |Cite
|
Sign up to set email alerts
|

In patients with metastatic breast cancer the identification of circulating tumor cells in epithelial-to-mesenchymal transition is associated with a poor prognosis

Abstract: BackgroundAlthough recent models suggest that the detection of Circulating Tumor Cells (CTC) in epithelial-to-mesenchymal transition (EM CTC) might be related to disease progression in metastatic breast cancer (MBC) patients, current detection methods are not efficient in identifying this subpopulation of cells. Furthermore, the possible association of EM CTC with both clinicopathological features and prognosis of MBC patients has still to be demonstrated. Aims of this study were: first, to optimize a DEPArray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 40 publications
8
104
0
Order By: Relevance
“…In patients with advanced non-small cell lung cancer, the majority of isolated or clustered CTCs harbor a dual epithelial/mesenchymal phenotype, and only some CTCs express exclusively vimentin or fibronectin [140] . Importantly, a fraction of cells coexpressing epithelial and mesenchymal markers was associated with poorer PFS and OS in MBC [142] . In lung cancer patients it was shown that radiotherapy can induce release of single CTCs or CTC clusters [143] .…”
Section: Clinical Significance Of Emt In Ctcsmentioning
confidence: 95%
“…In patients with advanced non-small cell lung cancer, the majority of isolated or clustered CTCs harbor a dual epithelial/mesenchymal phenotype, and only some CTCs express exclusively vimentin or fibronectin [140] . Importantly, a fraction of cells coexpressing epithelial and mesenchymal markers was associated with poorer PFS and OS in MBC [142] . In lung cancer patients it was shown that radiotherapy can induce release of single CTCs or CTC clusters [143] .…”
Section: Clinical Significance Of Emt In Ctcsmentioning
confidence: 95%
“…On the other side, the EpCAMlow/− fraction of CTCs alone has not been shown to correlate with patient outcome (53). Consistently, in other types of metastatic tumors, mesenchymal CTCs alone have been only weakly associated with OS and PFS (78). All together, these data suggest that a complementary dual technology, detecting both epithelial and mesenchymal CTCs might allow to obtain a much clear picture of the potential of these cells in predicting patient outcome (18).…”
Section: The Long Road Towards Clinical Utilitymentioning
confidence: 54%
“…In order to circumvent the issue of heterogeneous expression of EpCAM on tumor cells, Bulfoni and group adopted a CTC enrichment strategy based on red blood cell lysis followed by the immunomagnetic depletion of leukocytes from blood samples (i.e., a negative selection) and subsequently stained the recovered cells with a cocktail of antibodies recognizing epithelial and mesenchymal markers and sorted them by multiparametric fluorescence. They found presence of CTCs co-expressing epithelial and mesenchymal markers (EM CTC) were significantly associated with poorer progression free survival and overall survival [132]. Zhang et al [133], used anti-CD45 antibodies to deplete CD45 positive cells and enrich CTCs in blood collected from pancreatic cancer patients followed by immune-staining of CK and CD45, DAPI and fluorescence in situ hybridization with the centromere of chromosome 8 (CEP8) probe to identify CTCs in 31 cases of pancreatic cancers, and 30 healthy individuals.…”
Section: Methods To Isolate and Identify Ctcmentioning
confidence: 99%